Hackenfeller's ape - Brophy, Brigid 1929-1995 (Faber & Faber, 2023)
In London Zoo, Professor Darrelhyde is singing to the apes again. Outside their cage, he watches the two animals, longing to observe the mating ritual of this rare species. But Percy, inhibited by confinement and melancholy, is repulsing Edwina's desirous advances. Soon, the Professor's connection increases as he talks, croons, befriends. So when a scientist arrives on a secret governmental mission to launch Percy into space, the Professor vows to secure his freedom - but when met by society's indifference, he takes matters into his own hands . . . A trailblazing animal rights campaigner, Brigid Brophy's sensational 1953 novel is as provocative and philosophical seventy years on. An electric moral fable, it is as much a blazingly satirical reflection on homo sapiens as the non-human - on our capacity for violence, red in tooth and claw, not only to other species, but our own.
First published in 1953 by Rupert Hart-Davis
Keywords: Zoo animals / England / London / Fiction; Apes / England / London / Fiction; Apes; Zoo animals; Fiction; Novels; England - London; Fiktionale Darstellung